Punching shear strength of reinforced concrete column footings under eccentric compression: Experiment and analysis. (1st November 2019) - Zhang, Wang-Xi; Li, Bo; Hwang, Hyeon-Jong; Zhang, Jin-Yi; Xiao, Long-Jie; Yi, Wei-jian; Park, Hong-Gun
Highlights: Rubber-wooden composite blocks to simulate and measure the reaction of soil foundation. The effect of flexural bars on the punching shear strength of the column footing under eccentric load. Punching shear failure in the column footing with low flexural reinforcement ratio. A new prediction model for the punching shear strength of the column footing under eccentric load. Abstract: In reinforced concrete (RC) column footings, the soil stiffness can significantly affects the punching shear strength of the foundation slab. The present study conducted eccentric compression tests on three RC column footings considering the complex interaction between the soil and structure, and investigated the load-carrying capacity, displacement distribution, reaction distribution, failure mode, crack development, and strain distribution. The test parameter was flexural reinforcement ratio in the foundation slab. The test results showed that the footing specimen with lower reinforcement ratio was susceptible to brittle punching shear failure, and the flexural reinforcement ratio affected the crack distribution and the spalling of concrete cover. Since only one specimen was used in each flexural reinforcement ratio, however, the test results should be carefully considered. On the basis of the test results including existing studies, the effect of design parameters on the punching shear strength was evaluated. As a result, a new method was developed to predict the punching shear strength by addressing the eccentric compression force.